A reinterpretation of critical flicker-frequency (CFF) data reveals key details about light adaptation and normal and abnormal visual processing. (March 2022) - Rider, Andrew T.; Henning, G. Bruce; Stockman, Andrew
Abstract: Our ability to see flicker has an upper frequency limit above which flicker is invisible, known as the "critical flicker frequency" (CFF), that typically grows with light intensity ( I ). The relation between CFF and I, the focus of nearly 200 years of research, is roughly logarithmic, i.e., CFF ∝ log (I) —a relation called the Ferry-Porter law. However, why this law should occur, and how it relates to the underlying physiology, have never been adequately explained. Over the past two decades we have measured CFF in normal observers and in patients with retinal gene defects. Here, we reanalyse and model our data and historical CFF data. Remarkably, CFF- versus - I functions measured under a wide range of conditions in patients and in normal observers all have broadly similar shapes when plotted in double-logarithmic coordinates, i.e., log (CFF)- versus -log( I ). Thus, the entire dataset can be characterised by horizontal and vertical logarithmic shifts of a fixed-shape template. Shape invariance can be predicted by a simple model of visual processing built from a sequence of low-pass filters, subtractive feedforward stages and gain adjustment (Rider, Henning & Stockman, 2019). It depends primarily on the numbers of visual processing stages that approach their power-law region at a given intensity and a frequency-independent gain reduction at higher light levels. Counter-intuitively, the CFF- versus-I relation depends primarily on the gain of the visual response rather than its speed—a conclusion that changes our understanding and interpretation of human flicker perception. The Ferry-Porter "law" is merely an approximation of the shape-invariant template.